Status of Sound Pollution and its Impact on Human Health in Dhading Besi - Adhikari, Nisha; Singh, Reeta; Chauhan, Raju (Journal of Environment Sciences, 2025)
This study focuses on noise status and its impact on human health, in Neelakantha Municipality Ward No. 3 of Dhading Besi. Eleven sites in three different areas were selected as high-traffic, commercial, and residential zones of Dhading Besi. The Sound Level Meter was used to measure with the replicate of five times at each location between 6 am to 7 pm in January 2023 A.D. The health impact of people was assessed among 102 respondents of different categories residing in the study area through a questionnaire-based survey. Result shows that most of the location’s average sound level was above the sound level standard prescribed by the Government of Nepal and World Health Organization. From this study, the average sound level of Dhading Besi was measured as 68 dB (A) and that of commercial, high-traffic, and residential areas were 70 dB (A), 72 dB (A), and 63 dB (A) respectively. Average noise was maximum at Puchar bazaar 76 dB (A) in a high-traffic area and the minimum was observed at Ganesh Marg 61 dB (A) in a residential area. In high-traffic areas, the sound level was maximum in the afternoon non-peak hour (12 pm to 1 pm) at 76 dB (A). At all three-area; high-traffic, commercial, and residential area minimum sound level was observed at morning non-peak hour time 66 dB (A), 61 dB (A), and 56 dB (A) respectively. The primary health impacts of noise, as revealed by the questionnaire survey, are headache, irritation, and stress, followed by communication issues, sleep disturbances, and hearing issues. This study serves as a baseline of noise level in the growing suburbs of Dhading and helps to develop the environmental policy for controlling noise pollution.